THE MANAGEMENT OF HIGH BLOOD PRESSURE THROUGH QURANIC VERSES AND EXERCISE - Najmul Sahar Ilyas; Syeda Rida Baqir; Komal Jamil (International Journal of Islamic and Complementary Medicine, 2025)
High Blood Pressure (HBP) is defined as the consistent rise in blood pressure pushing against an artery's walls. It is the most common cause of cardiovascular disease and mortality in the United States. Recitation from the Quran is indeed a form of Islamic spiritual healing. It is believed to be a means of seeking protection and healing through reciting verses from the Quran, including specific chapters such as Surah al-Fatiha, Surah Al-Falaq, and Surah An-Nas. Exercise has been shown to be effective in preventing and maintaining Hypertension. This article aims to explore the information related to the treatment of hypertension through Quranic Verses and exercise. The literature review was done by collecting data from various search websites like PubMed, Google Scholar, Scihub, etc. This study is used to enhance awareness regarding the effectiveness of Quranic verses and exercises for treating HBP through the evidence-based practice approach. We concluded that Quranic verses proved to be a source of treatment and guidance for patients with hypertension, along with medicine. However, using exercise can provide an effective way of maintaining and preventing High Blood Pressure (HBP) ABSTRAK Hipertensi adalah peningkatan tekanan darah yang terus menerus yang mendorong dinding arteri. Ini adalah penyebab paling umum dari penyakit kardiovaskular dan kematian di Amerika Serikat. Pembacaan ayat-ayat suci Al-Quran merupakan salah satu bentuk terapi spiritual Islam. Hal ini diyakini sebagai sarana untuk mencari perlindungan dan penyembuhan melalui pembacaan ayat-ayat Al-Quran, termasuk bab-bab tertentu seperti Surat Al-Fatihah, Surat Al-Falaq dan Surat An-Nas. Olahraga juga efektif dalam pencegahan dan pemeliharaan Hipertensi. Tujuan dari artikel ini adalah mengeksplorasi informasi yang berkaitan dengan pengobatan hipertensi melalui ayat-ayat Al-Quran dan olahraga. Tinjauan literatur dilakukan melalui pengumpulan berbagai situs pencarian seperti Pubmed, Google Scholar, Scihub, dll. Studi ini digunakan untuk meningkatkan kesadaran mengenai efektivitas ayat-ayat Al-Quran dan olahraga untuk pengobatan Hipertensi melalui pendekatan praktik berbasis bukti. Kami menyimpulkan bahwa ayat-ayat Al-Quran terbukti menjadi sumber pengobatan dan bimbingan bagi pasien hipertensi bersama dengan obat-obatan. Namun penggunaan olahraga dapat memberikan cara yang efektif untuk menjaga dan mencegah hipertensi.